The Impact of Works Councils on Wages - Addison, John T. (2006)
This paper investigates for the first time the effect of works councils on the anatomy of wages, using matched employer-employee data from the German LIAB for 2001. We find that works councils are associated with higher earnings. The wage premium is roughly comparable with the combined effect of sectoral and plant collective bargaining proper. This result persists after taking account of worker and establishment heterogeneity and the endogeneity of works council presence. Next, using quantile regressions, we find that the works council premium is decreasing with the position of the worker in the wage distribution. And it is also higher for women than for men. Finally, in addition to attenuating the gender wage gap and reducing wage dispersion, works councils have a small but significantly positive impact on tenure after controlling for wages. This suggests that there is some rent sharing; even if, overall, the entity’s voice effects appear to dominate its monopoly effects.